A Severe Dementia Syndrome Caused by Intron Retention and Cryptic Splice Site Activation in STUB1 and Exacerbated by TBP Repeat Expansions - Reis, Marlen Colleen; Patrun, Julia; Ackl, Nibal; Winter, Pia; Scheifele, Maximilian; Danek, Adrian; Nolte, Dagmar (Frontiers in Molecular Neuroscience, 2022)
Heterozygous pathogenic variants in the STIP1 homologous and U-box containing protein 1 (STUB1) gene have been identified as causes of autosomal dominant inherited spinocerebellar ataxia type 48 (SCA48). SCA48 is characterized by an ataxic movement disorder that is often, but not always, accompanied by a cognitive affective syndrome. We report a severe early-onset dementia syndrome that mimics frontotemporal dementia and is caused by the intronic splice donor variant c.524+1G>A in STUB1. Impaired splicing was demonstrated by RNA analysis and in minigene assays of mutated and wild-type constructs of STUB1. The most striking consequence of this splicing impairment was retention of intron 3 in STUB1, which led to an in-frame insertion of 63 amino acids (aa) (p.Arg175_Glu176ins63) into the highly conserved coiled-coil domain of its encoded protein, C-terminus of HSP70-interacting protein (CHIP). To a lesser extent, activation of two cryptic splice sites in intron 3 was observed. The almost exclusively used one, c.524+86, was not predicted by in silico programs. Variant c.524+86 caused a frameshift (p.Arg175fs*93) that resulted in a truncated protein and presumably impairs the C-terminal U-box of CHIP, which normally functions as an E3 ubiquitin ligase. The cryptic splice site c.524+99 was rarely used and led to an in-frame insertion of 33 aa (p.Arg175_Glu176ins33) that resulted in disruption of the coiled-coil domain, as has been previously postulated for complete intron 3 retention. We additionally detected repeat expansions in the range of reduced penetrance in the TATA box-binding protein (TBP) gene by excluding other genes associated with dementia syndromes. The repeat expansion was heterozygous in one patient but compound heterozygous in the more severely affected patient. Therefore, we concluded that the observed severe dementia syndrome has a digenic background, making STUB1 and TBP important candidate genes responsible for early-onset dementia syndromes.